Eagle Mountain Observatory: Eagle Mountain, Minnesota - Mark Banholzer (Oz, 1986)
Our contemporary understanding of the universe has become a rational and systematic science, separating man as a casual onlooker in the scheme. Ancient man on the other hand, believed the universe to be a delicate balance of earth, sky, and man. The blending of these three elements lends a richness that is absent in our modem interpretation...